Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4102/ajlm.v5i1.381
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating laboratory request forms submitted to haematology and blood transfusion departments at a hospital in Northwest Nigeria

Abstract: BackgroundThe laboratory request form (LRF) is a communication link between laboratories, requesting physicians and users of laboratory services. Inadequate information or errors arising from the process of filling out LRFs can significantly impact the quality of laboratory results and, ultimately, patient outcomes.ObjectiveWe assessed routinely-submitted LRFs to determine the degree of correctness, completeness and consistency.MethodsLRFs submitted to the Department of Haematology (DH) and Blood Transfusion S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
14
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 20 publications
8
14
10
Order By: Relevance
“…There were only 1.0% (3/289) of the evaluated request forms with all the required information and the rest had one or more of the parameters missing. This result is similar to the finding by Oyedeji et al [9] and Oyelekan et al [10] [12] reported a similar finding. The time of collection of the specimen was indicated in 84.1% of the forms and this was higher than the findings reported in studies by Adekoge et al [13], Makubi et al [8], Oyelekan et al [10] and Olayemi & Asiamah-Broni [11] where the parameter was recorded in 10.3%, 1.5%, 0.7% and 0.0% of the request forms respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There were only 1.0% (3/289) of the evaluated request forms with all the required information and the rest had one or more of the parameters missing. This result is similar to the finding by Oyedeji et al [9] and Oyelekan et al [10] [12] reported a similar finding. The time of collection of the specimen was indicated in 84.1% of the forms and this was higher than the findings reported in studies by Adekoge et al [13], Makubi et al [8], Oyelekan et al [10] and Olayemi & Asiamah-Broni [11] where the parameter was recorded in 10.3%, 1.5%, 0.7% and 0.0% of the request forms respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of clinical information, the diagnosis was filled in 85.8% of the request forms and this finding compares with the that by Nutt et al [16] of 80.9% but higher than the result by Makubi et al [8] of 37.9%. The clinical history was indicated in 14.9% of the forms and it is lower than the one reported by Makubi et al [8] Clinician's name and sign were available in 96.9% and 96.5% of the evaluated forms respectively and this finding is similar to that from studies by Oyelekan et al [10] and Jegede et al [12] where both the parameters were present in 93.8%…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, 40.1% of the request forms observed did not state the date of sampling. This was comparable to results obtained in a similar study conducted in Ghana (37.3%) ( 21 ), but, higher than results obtained in Nigeria (0.5%) ( 23 ). This variation could be attributed to the workload on physicians, attitudinal difference and negligence among physicians, lack of monitoring by the concerned body or improper orientation about the impact of incomplete test request form on the quality of patient care.…”
Section: Discussionsupporting
confidence: 88%
“…7 Another study compared the requests generated by the Department of Haematology (DH) and Blood Transfusion Services (BTS) of Aminu Kano Teaching Hospital, Kano, Nigeria. 8 Overall, component request form completeness was 89.5% for DH and 81.2% for BTS. The level of completeness of both forms were suboptimal and there was a need to re-design the request form according to international guidelines and to review specimen rejection practices.…”
Section: Discussionmentioning
confidence: 95%